2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091246
|View full text |Cite
|
Sign up to set email alerts
|

EEG preprocessing for synchronization estimation and epilepsy lateralization

Abstract: The global framework of this paper is the synchronization analysis in EEG recordings. Two main objectives are pursued: the evaluation of the synchronization estimation for lateralization purposes in epileptic EEGs and the evaluation of the effect of the preprocessing (artifact and noise cancelling by blind source separation, wavelet denoising and classification) on the synchronization analysis. We propose a new global synchronization index, based on the classical cross power spectrum, estimated for each cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These works attempt to find the optimal order that the techniques have to be applied in order to not miss relevant information about seizures. They concluded that the first processing step should be BSS (to identify artifact sources) and then WD (to eliminate additive noise) [68,69].…”
Section: Independent Component Analysismentioning
confidence: 99%
“…These works attempt to find the optimal order that the techniques have to be applied in order to not miss relevant information about seizures. They concluded that the first processing step should be BSS (to identify artifact sources) and then WD (to eliminate additive noise) [68,69].…”
Section: Independent Component Analysismentioning
confidence: 99%